FUNGSI KARTUN PADA ZAMAN DAHULU P - St. Rahmah (Multilingual, 2016)
The problem in this research is the study of literature psychoanalytic to thefunction of cartoon Pada Zaman Dahulu for children. The aims of thisresearch is to discover, to collect, then to describ the functions of cartoon PadaZaman Dahulu for children. The method used is qualitative by library research,which is analyzed by descriptive analytic and informal methods. The resultsindicates that the functions and influences of cartoon figures as theentertainment media education, the preservation of the folklore, to trainchildren's creativity, the capture power train children, instilling values, andcommunication media for children.